(untitled) (Zaporizhzhia Historical Review, 2021)
One of the works of well-known Ukrainian figures, historian, archivist and academic Volodymyr Ivanovych Scherbyna (1850-1936), at present wrongly forgotten, is taken as the object of current research. It serves as an example of forming the creative outlook and skills of the historian.